Inequality measures for wealth distribution: Population vs individuals perspective - Pascoal, R. (2018)
Economic inequality is, nowadays, frequently perceived as following a growing trend with impact on political and religious agendas. However, there is a wide range of inequality measures, each of which pointing to a possibly different degree of inequality. Furthermore, regardless of the measure used, it only acknowledges the momentary population inequality, failing to capture the individuals evolution over time. In this paper, several inequality measures were analyzed in order to compare the typical single time instant degree of wealth inequality (population perspective) to the one obtained from the individuals’ wealth mean over several time instants (individuals perspective). The proposed generalization of a simple addictive model, for limited time average of individual’s wealth, allows us to verify that the typically used inequality measures for a given snapshot instant of the population significantly overestimate the individuals’ wealth inequality over time. Moreover, that is more extreme for the ratios than for the indices analyzed.